Zhuanggu Guanjie herbal formula mitigates osteoarthritis via the NF-κB transduction mechanism - Guowei, Gong; Yuzhong, Zheng; Xuan, Zhou; Zhi, Dai; Juanhui, Duan; Jing, Wang; Peikui, Yang; Xiangzhi, Liu; Zhen, Wen (Frontiers in Pharmacology, 2022)
The Zhuanggu Guanjie herbal formula has been a famous Chinese prescription for treating bone diseases since time immemorial. The anti-osteoarthritis (OA) properties of this botanical prescription are well documented in the Chinese Pharmacopoeia. However, the detailed mechanisms behind the phenomenon have not been elucidated. Hence, we aimed to investigate the anti-OA efficacy of the Zhuanggu Guanjie herbal formula and its underlying mechanism. The anti-OA properties of Zhuanggu Guanjie capsule (ZGC) were determined by the cytokine contents and inflammatory-related proteins, which were measured by RT-PCR, flow cytometry, Western blot, and laser confocal assay in ATDC5 cells. The levels of interleukin-6, tumor necrosis factor-α, inducible nitric oxide synthase, cyclooxygenase-2, and prostaglandin synthesis E2 have been markedly reduced after being treated with ZGC for 48 h in a dose-dependent manner. Furthermore, ZGC prevented the translocation of NF-κB from the cytosol to the nucleus. On the other hand, we used the mono-iodoacetate (MIA)-induced OA model to confirm the in vivo efficacies of this herbal formula. Oral administration of ZGC attenuated MIA-induced OA damage through changes in histopathological and knee joint volumes. The serum matrix metalloproteinase-13 contents in the ZGC treatment group declined as compared to those in the MIA model group. Through our in vitro and in vivo studies, we confirmed the anti-OA efficacy of ZGC and uncovered its detailed mechanism, and this treatment shed light on OA pathophysiology.